Immunotherapies in Huntington's disease and α-Synucleinopathies - Fatoba, Oluwaseun; Ohtake, Yosuke; Itokazu, Takahide; Yamashita, Toshihide (Frontiers in Immunology, 2020)
Modulation of immune activation using immunotherapy has attracted considerable attention for many years as a potential therapeutic intervention for several inflammation-associated neurodegenerative diseases. However, the efficacy of single-target immunotherapy intervention has shown limited or no efficacy in alleviating disease burden and restoring functional capacity. Marked immune system activation and neuroinflammation are important features and prodromal signs in polyQ repeat disorders and α-synucleinopathies. This review describes the current status and future directions of immunotherapies in proteinopathy-induced neurodegeneration with emphasis on preclinical and clinical efficacies of several anti-inflammatory compounds and antibody-based therapies for the treatment of Huntington's disease and α-synucleinopathies. The review concludes with how disease modification and functional restoration could be achieved by using targeted multimodality therapy to target multiple factors.